The peculiarities of Rivne region tourism infrastructure functioning - Andrii Slashchuk; Halyna Bernadska (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
In the article, the current state and peculiarities of Rivne region tourism infrastructure functioning have been analysed; the perspective directions of development have been defined. The main elements of tourism infrastructure are as follows: hotel restaurant businesses, trade establishments, tourism enterprises, transport connection, gas and petrol stations, means of communication, culture and entertainment establishments, bank system etc. Among the places of accomodations, children summer health and leisure enterprises dominate – 126, hotels and analogous means of accomodations comprise 15, other enterprises -3. The summary number of places is 1858. The restaurant sphere of the region is rather developed. In Rivnenschina, cafеs prevail – 798, cafeterias comprise 245, bars – 172, restaurants – 64, other enterprises – 241. 116 tourism enterprises conduct tourism activity. Among them 3 tour operators, 104 tour agents and 9 participants conducting excursion activity. The highest concentration of the tourism activity participants is observed in Rivne, Varash, Dubno, and in Rivne region. The network of cultural educational institutions comprises 2 regional theaters – Academic Ukrainian Music and Drama Theatre and Puppet Theatre, Regional Philharmonia, 590 public and public school libraries, 671 clubs and houses of culture, 5 cinemas, 14 state museums and historic cultural reserves, the Reginal Folk Art Center, the Culture and Rest Park and the Zoo. Economic complex and the country's population transport service are conducted by the three means of transportation: automobile, railway and air. The best tourism infrastructure provision is in Rivne, Dubno, Varash, Ostroh, and also in Rivne, Volodymyrets, Sarny, Bereznivs'k regions. The important directions of development are existant TI element improvement and creation of new ones, investation involvement, the Rivne Region international tourism market entrance.